Plasma levels of protein C pathway proteins and brain magnetic resonance imaging volumes in multiple sclerosis. (8th September 2019) - Ziliotto, N.; Zivadinov, R.; Baroni, M.; Marchetti, G.; Jakimovski, D.; Bergsland, N.; Ramasamy, D. P.; Weinstock‐Guttman, B.; Straudi, S.; Manfredini, F.; Ramanathan, M.; Bernardi, F.
Abstract : Background and purpose: The involvement of protein C (PC) pathway components in multiple sclerosis (MS) has scarcely been explored. The aim was to investigate their levels in relation to clinical and neurodegenerative magnetic resonance imaging (MRI) outcomes in patients. Methods: In all, 138 MS patients and 42 healthy individuals were studied. PC, protein S (PS) and soluble endothelial protein C receptor (sEPCR) were evaluated by multiplex assays and enzyme‐linked immunosorbent assay. Regression analyses between 3 T MRI outcomes and PC pathway components were performed. ancova was used to compare MRI volumes based on protein level quartiles. Partial correlation was assessed amongst levels of PC pathway components and hemostasis protein levels, including soluble thrombomodulin (sTM), heparin cofactor II (HCII), plasminogen activator inhibitor 1 (PAI‐1) and factor XII (FXII). The variation of PC concentration across four time points was evaluated in 32 additional MS patients. Results: There was an association between PC concentration, mainly reflecting the zymogen PC, and MRI measures for volumes of total gray matter (GM) ( P  =   0.003), thalamus ( P  =   0.007), cortex ( P  =   0.008), deep GM ( P  =   0.009) and whole brain ( P  =   0.026). Patients in the highest PC level quartile were characterized by the lowest GM volumes. Correlations of PC–HCII, PC–FXII and sEPCR–sTM values were detectable in MS patients, whilst PC–PS and PS–PAI‐1 correlations were present in healthy individuals only. Conclusions: Protein C plasma concentrations might be associated with neurodegenerative MRI outcomes in MS. Several differences in correlation amongst protein plasma levels suggest dysregulation of PC pathway components in MS patients. The stability of PC concentration over time supports a PC investigation in relation to GM atrophy in MS.